Human greatness according to Brooks in family, school and community systems - Llanos Zuloaga, Martha (2025)
The present study completes the trilogy of articles related to Human Greatness, the first two published in thejournal Advances in Psychology (Llanos, 2023 and 2024) involved an extensive theoretical review, bringingus closer to the topic and presenting not only the conceptual description of various authors but also aimingfor a dynamic approach to the different philosophical, psychological, and educational perspectives. Thetriangulation of the systems most involved in the exercise of human greatness, such as the family, the school,and society or community, geared to a preliminarily contact with representatives of the mentioned systems asbasic foundations of human greatness.This article presents the results of the application of George Brooks’ (2020) proposal on what he calls the 8Great Values of Human Greatness. It is a preliminary exploratory survey in this field, taking four groups whoseroles are linked to the educational field of childhood and youth. They are kindergarten and primary schoolteachers, mothers, artists, and other professions related to education.We share the analysis of the results as a starting point for an empirical approach to the topic and only toidentify trends that motivate a deeper study on the subject of Human Greatness, its values, and its connectionswith the educational triad that integrates the family, school, and community systems.We found that meaningful purpose, collective cooperation, trust, and compassion are the values identified asindicators of Human Greatness.